Coordinated regulation of timing and strength of synaptic outputs by adrenergic receptors through control of action potentials in Purkinje cells - Furukawa, Kei; Kawaguchi, Shin-ya (Frontiers in Cellular Neuroscience, 2025)
In contrast to conventional view about the faithful signaling in neuronal axons by all-or-none action potentials, recent studies have shown that axons exhibit dynamic change in action potential waveforms and/or conduction velocities in a manner dependent on neuronal activity and/or inputs to axonal compartments from other neurons. It was recently shown that a well-known second messenger cAMP negatively regulates the axonal voltage-gated Na+ channels, which decreases the amplitude and conduction velocity of action potentials in axons of cerebellar Purkinje cells. To understand the signaling mechanism and physiological context of the cAMP-mediated action potential modulation, we studied the involvement of one of neuromodulators, adrenergic system, using direct patch-clamp recordings from axons and/or terminals of Purkinje cells. We demonstrate that Purkinje cell axons exhibit negative control of action potentials in amplitude and conduction velocity by β-adrenergic receptors in a manner dependent on the axonal length through specific reduction of axonal Na+ currents. On the other hand, β-adrenergic receptors increased presynaptic release probability without changing the amount of readily releasable vesicles in axon terminals of Purkinje cells. Together, our data highlight a physiological pathway to activate cAMP signaling to cause the axonal length-dependent dynamic changes in the timing and strength of synaptic transmission.